(untitled) (E Conference Zone, 2024)
This article analyzes the terms of the Uzbek language by dividing them into thematic and lexical-semantic groups. The types of Uzbek theater that existed in the past in the form of street performances and new names that have a modern appearance are considered in terms of diachronic and synchronous nature.